Structural and electrochemical characterization of diatomite with lignin, glucose, activated carbon and magnetic nanoparticles - Maria Silva; Sarah Briceño; Karla Vizuete; Alexis Debut; Gema González (Carbon Trends)
This work explores the synthesis and characterization of Diatomite-based composites and the effect of the carbon source (Glucose, Lignin, and Activated Carbon) along with magnetic nanoparticles on the structural and electrochemical properties. The samples were characterized using X-ray diffraction (XRD), Energy Dispersive spectroscopy (EDS), Raman spectroscopy, Electrochemical Impedance spectroscopy (EIS), and Cyclic voltammetry. Our results reveal that the glucose composite exhibited the highest conductivity and electrochemical performance compared to those made with lignin and activated carbon due to forming iron carbide and graphite-like structures. These findings suggest that selecting carbon sources and incorporating magnetic nanoparticles optimize diatomite-based materials for potential applications as electrode materials.